TARGETING THE MAIN PROTEASE AND THE SPIKE PROTEIN OF SARS-COV-2 WITH NATURALLY OCCURRING COMPOUNDS FROM SOME CAMEROONIAN MEDICINAL PLANTS: AN IN-SILICO STUDY FOR DRUG DESIGNING - Fouedjou , Romuald Tematio; Dongmo Fogang, Hervet Paulain; Ouassaf, Mebarka; Qais, Faizan Abel; Bakhouch, Mohamed; Belaidi, Salah; Chtita, Samir (Journal of the Chilean Chemical Society, 2022)
Despite the social distancing and hygiene rules prescribed by the WHO, the novel Corona-virus is still on the way of a significant rapid rise in deaths. Therefore, identification of chemotherapeutic drugs against Corona Viral Infection all around the world is still requires. Some medicinal plants have a valuable therapeutic effect when mixt with honey, the obtained formulations are preliminary use in Cameroon against viral infection particularly respiratory infections. In this work, we looked for the potential anti-SARS-CoV-2 molecule throw execution of in silico computational studies of six Cameroonian plants intervening in the treatment respiratory infections in apiphytotherapy. AutoDock Vina was used for docking studies against SARS-CoV-2 Mpro and SP. We further conducted of pharmacokinetics properties and the safety profile of compounds with the top score in order to identify the best drug candidates. Totally 100 compounds were screened, of these, eighteen showed high binding affinity against SARS-CoV-2 Mpro and SP. The results suggest the effectiveness of compounds 10 and 17 obtained from Citrus Sinensis as potent drugs against SARS-CoV-2 as they tightly bind to its Mpro and SP with low binding energies. The stability of the two compounds complexed with Mpro and SP was validated through MD simulation. The availability of potent protein inhibitors and diverse of compounds from Cameroon flora scaffolds indicate the feasibility of developing potent main protease and spikes proteins inhibitors as antivirals for COVID-19. Based on further in vivo and in vitro experiments and clinical trials, some of these phytoconstituents could be proposed for effective inhibition of the replication of the SARS-CoV-2.